QUALITY OF LIFE OF THE OLD PEOPLE OF SANTA TEREZINHA - PB (Fiep Bulletin - online, 2019)
Life expectancy has grown considerably in recent times. New lifestyles tell us that the average age of the human beingextends to each day. In this way, it is necessary to create a social scenario capable of contributing to the autonomy and independenceof these individuals, so that they remain active and participatory in society, and not lose their self-esteem. The present study aims toanalyze the quality of life of the elderly in the city of Santa Terezinha (PB). The study is characterized in a field research of exploratorycharacter and qualitative approach, however does not perform numerical measurement and the analysis is not statistical. The targetpopulation was 20 elderly people and the research instrument used was the SF-36 (Short-Form 36 Health Survey) (1999)questionnaire, in which we evaluated its eight domains: functional capacity; physical aspects; emotional aspects; pain; general healthstatus; vitality; social aspects and mental health. Taking into account the values from 0 to 100 (0 = worse, 100 = best result) thefollowing results were obtained: social aspects (86.3), mental health (81.6), vitality (74.5), general condition (71.5), limitation byemotional aspects (70), limitation by physical aspects (70), functional capacity (64.5) and pain (62). The results allow concluding thatthe elderly of the municipality of Santa Terezinha - PB presented high scores in the pain and limitation areas due to emotional andphysical aspects, but the other domains had significant results.